2022
DOI: 10.1021/jasms.2c00022
|View full text |Cite
|
Sign up to set email alerts
|

Postcolumn Infusion as a Quality Control Tool for LC-MS-Based Analysis

Abstract: Postcolumn infusion has been widely used to study the matrix effect of analytical methods based on liquid chromatography coupled to mass spectrometry (LC-MS). Nevertheless, this methodology is usually only applied during a method development or validation. With this application note, we aim to demonstrate that the continuous use of postcolumn infusion can be also a very useful tool to monitor the quality of LC-MS analyses and easily detect flaws in the analytical method performance. Here we propose a protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Blank plasma and zero samples were also prepared and analyzed. All analytical standards and QC samples were stored at −20 °C before use . AMX calibration curves were prepared in the blank brain matrix, where 5 mg of brain tissue was added to 1 mL of phosphate-buffered saline with a pH of 7.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blank plasma and zero samples were also prepared and analyzed. All analytical standards and QC samples were stored at −20 °C before use . AMX calibration curves were prepared in the blank brain matrix, where 5 mg of brain tissue was added to 1 mL of phosphate-buffered saline with a pH of 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…All analytical standards and QC samples were stored at −20 °C before use. 53 AMX calibration curves were prepared in the blank brain matrix, where 5 mg of brain tissue was added to 1 mL of phosphate-buffered saline with a pH of 7.4. Samples were homogenized using an IKA T10 (Staufen, Germany) for 30 s and then centrifuged at 10,000 rpm for 10 min at 4 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…For the matrix effect assessment and correction, the postextraction spiking method is more suitable for targeted metabolomics due to the requirement of authentic standards. Hence, PCI is recommended as a more appropriate tool for matrix effect evaluation in untargeted metabolomics, , but only few studies about its application have been reported. , Although stable isotope labeling has also been applied to matrix effect evaluation in untargeted metabolomics, this technique is limited to specific sample types like yeast, cells, or plants due to the requirement of a globally labeled growth medium. …”
Section: Introductionmentioning
confidence: 99%